EFFECT OF INPUTS ON ELECTROPHYSICAL AND THERMOELECTRIC PROPERTIES OF GRANULAR SILICON - Sokhibova Zarnigorkhon Mutalibjon kizi (Лучшие интеллектуальные исследования, 2024)
Abstract. This paper discusses the effect of additives on the electrophysical and thermoelectric properties of silicon-based thermoelectric materials and thermocouples. Increasing the thermoelectric, electrophysical and radiation resistance properties of nano- and micro-sized semiconductor materials, as well as the effect of alkali metals on them, the dependence of the physical properties of granulated semiconductors on thermal voltaic effects, and the mechanisms of manifestation of these effects were studied.